The Competence of Nurses in Performing Maternal and Child Health Care Practices According to Islamic Principles: A Case Study in the Three Southern Border Provinces - Yama, Malinee; Kaewsan, Pattaya (Princess of Naradhiwas University Journal, 2026)
Background and Objectives The implementation of maternal and child health services in the three southern border provinces is complex due to the multicultural context and religious beliefs. This study aimed to examine the competencies of professional nurses that align with maternal and child health care practices according to Islamic principles to ensure that health services were in harmony with the lifestyle and effectively meet the needs of the local population. Methods This study was qualitative descriptive research. Key informants were purposefully selected, totaling 14 participants, including: 1) Eight professional nurses and public health administrators, each with more than 10 years of experience in maternal and child health care in the area, were included in the study. 2) One provincial religious leader, 3) Two traditional midwives with more than 10 years of experience, and 4) Three people from a group of service users. The research tool used was a semi-structured in-depth interview guide, with the researcher as the primary data collector. Data were analyzed using content analysis, and their reliability was verified through triangulation. Results The study on the competencies of nurses in maternal and child health care practices in the three southern border provinces according to Islamic principles, conducted through qualitative research using content analysis, found that the most important competency was the integration of professional nursing skills with services that respond to the cultural and Islamic religious context (transcultural care). These competencies included communication in local dialects, utilizing networks of religious and community leaders to foster understanding, respecting the beliefs and rights of service users, and involving families in health care decision-making. However, nurses also faced several significant challenges, including delays in the referral care system, vaccine refusal due to misunderstandings, and accumulated stress from workload and intensive indicators, resulting in the development of nursing competencies in this area. Balancing clinical excellence and cultural leadership was needed to create a service system that is accessible, safe, and sustainable in accordance with the lifestyle of the Muslim community. Conclusion and Recommendations To develop nursing competencies in the three southern border provinces, it is essential to integrate professional standards with the local context of beliefs, religion, and the specific situation. The research recommends that educational institutions and public health agencies incorporate Islamic healthcare practices and crisis communication skills as specialized competencies to create a culturally sensitive and highly effective nursing service system for the population.